Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 9 - 9.1 - Linear and Nonlinear Systems of Equations - 9.1 Exercise - Page 636: 29


$(0,0),$ $(-2,4)$

Work Step by Step

From the first equation, $y=x^{2}$ (Isolation). Consider the second equation, $2x+y=0$ This becomes: $2x+x^{2}=0$ (Substitution). Thus, $x^{2}+2x=0$ $x(x+2)=0$ This gives $x=0,$ and $x=-2$ Accordingly, $y=0,$ and $y=4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.